Antigua and Barbuda : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this paper, the following statistical data are listed in detail: savings and investment, indicators of construction activity, electricity generation, consumption, tariffs, consumer prices, estimates of population and labor force, operations of central government, detailed accounts of the consolidated public sector, public sector employment, monetary survey, summary accounts of commercial banks, selected interest rates, balance of payments, selected tourism statistics, external public sector debt, terms of external public sector loans, external debt excluding interest arrears, and distribution of commercial bank credit to the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet